Um ambiente virtual de aprendizagem suporte para o estudo de funções segundo a proposta curricular do estado de São Paulo - Piero, Pedro José Di (2011)
This paper describes the development of a virtual learning environment for teaching functions, with viewers created using the GeoGebra, constituting one of the products developed in the Professional Masters Program of the University of São Carlos. It is available in Moodle of the Mathematics Department of UFSCar, was created in four topics, one for each learning situation provided in the student diary volume 3 of the third grade of High School of the Secretaria of Education of the State of São Paulo .Each topic consists of activities like lessons, quizzes, sending files and participation in specific forums. The lessons seek to lead the student to acquire the skills provided in the Student notebook. The questionnaires are used to strengthen and verify that learning. The purpose of sending files and participating in the forums is to provide a self-evaluation and development of students' writing skills The environment does not change the principles guiding the curriculum of the State of São Paulo, keeping the content and context of encouraging the development of personal skills, especially those related to reading and writing mathematics. It is expected that the application of the environment, the use of the viewers, the participation in the forums and execution of activities and exercises with the aid of technology, encourage, motivate and facilitate the teaching and learning of mathematics, leading each participant to resize their concepts and knowledge. The participation of undergraduated students in the activities of virtual learning environment seeks to provide grants to train a teacher who can act as mediator, facilitator and challenger of learning, ready to work with students to construct their knowledge through manipulation, exploitation, navigation and communication with the "objects" presented.